2018
DOI: 10.1002/pam.22104
|View full text |Cite
|
Sign up to set email alerts
|

Housing Voucher Take‐Up and Labor Market Impacts

Abstract: Low participation rates in government assistance programs are a major policy concern in the United States. This paper studies take‐up of Section 8 housing vouchers, a program in which take‐up rates are quite low among interested and eligible households. We link 18,109 households in Chicago that were offered vouchers through a lottery to administrative data and study how baseline employment, earnings, public assistance, arrests, residential location, and children's academic performance predict take‐up. Our anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 46 publications
(101 reference statements)
0
10
0
Order By: Relevance
“…17 See Chyn, Hyman, and Kapustin (2019) and Currie and Yelowitz (2000) for discussions of this policy. 18 We have also estimated average causal responses (ACRs) for subsets in which many possible moves are induced.…”
Section: Estimation Results: Lates Of Neighborhood Qualitymentioning
confidence: 99%
“…17 See Chyn, Hyman, and Kapustin (2019) and Currie and Yelowitz (2000) for discussions of this policy. 18 We have also estimated average causal responses (ACRs) for subsets in which many possible moves are induced.…”
Section: Estimation Results: Lates Of Neighborhood Qualitymentioning
confidence: 99%
“…Many housing authorities ban those with heavy alcohol or drug use or criminal convictions (Curtis, Garlington, & Schottenfeld, 2013). Finally, those granted vouchers for use in the private market must find a landlord willing to accept the voucher, a factor that limits lease‐up rates among those with vouchers (Chyn, Hyman, & Kapustin, 2019).…”
Section: Methodsmentioning
confidence: 99%
“…The existing literature on public housing has largely focused on welfare implications, including effects on educational and health outcomes (Currie & Yelowitz, 2000;Jacob, 2004;Jacob et al, 2014;Olsen & Barton, 1983) and employment opportunities (Chyn, 2018;Chyn et al, 2019;Jacob & Ludwig, 2012). For example, Currie and Yelowitz (2000) found that public housing tenants are less likely to suffer overcrowding and their children tend to have better academic performance.…”
Section: Public Housing Programsmentioning
confidence: 99%